Hooke, Latour, and the History of Extended Cognition. - Silver, Sean (Eighteenth Century: Theory & Interpretation)
This essay considers the contemporary theory of extended cognition, also known as situated cognition, arguing that it began with the ideas set forth by English scientist Robert Hooke during the Restoration in London, England, and influencing French philosopher Bruno Latour and his notions on moderns, subject and object, and actor-network theory. Latour's works considered include the essay "On Actor-Network Theory: A Few Clarifications,” and the books "An Inquiry into Modes of Existence" and "Pandora’s Hope: Essays on the Reality of Science Studies."